miR-21 Expression in Grade I, II, and III Breast Cancer - -, Juwita; Ompusunggu, Henny E.S.; Nauphar, Donny; Pardede, Sumondang M.; Lim, Hadyanto; Siregar, Yahwardiah (Indonesian Journal of Medicine, 2016)
Background: Breast cancer is the second largest cancer in the world.The gold standard for breast cancer diagnosis and prognosis is grade assessment (mitotic, nuclear pleiomorphism, tubular formation), based on breast tissue histopathology. However, this assessment has limitation in that it is subjective and semi quantitative. A genetic biomarker known as Â microRNA (miRNA) may regulate human gene expression by targetting mRNA. One of the miRNA, i.e. miR-21, is able to suppress tumor suppressor mRNA, resulting in increased cellular proliferation andneoplastic transformation, and decreased apoptosis. This study aimed to investigate the expression of miR-21in breast cancer with histopathologic grade I, II, and III.Subjects and Method: This was a descriptive study with cross-sectional design involving paraffin block (FFPE) samples of ductal-type breast cancer tissue. Sixty four samples were obtained from the department of Anatomical Pathology, Haji Adam Malik Hospital, Medan. Patients history were obtained through medical records followed by sample processing (Total RNA Isolation, cDNA Synthesis, and Examination of miR-21 Expression using Real-Time qPCR). MiR-21 expression from every hystopathologic grade was obtained using Fold Change Calculation.Results: Breast cancer occurred more frequently in age group of 30-49 years old. Based on the histopathologic grade, most breast cancer was found in grade II. Analysis of miR-21 expression showed that miR-21 expression was higher in grade III compared to other grade.Conclusion: Breast cancer occured more frequently in the productive age group.Most breast cancer were found in grade II. Increased miR-21 expression in grade III may suggest that miR-21 is an oncomiR, which plays an important role in the development of malignant breast cancer.Keywords: breast cancer, histopathology grade, miRNA, miR-21.Correspondence:Â Juwita. Masters Program in Biomedical Sciences, Faculty of Medicine, North SumateraUniversity, Medan. Mobile: 08125262339.Indonesian Journal of Medicine (2016), 1(1): 26-33https://doi.org/10.26911/theijmed.2016.01.01.04